2018
DOI: 10.1021/acsaem.8b01209
|View full text |Cite
|
Sign up to set email alerts
|

Tin Oxides as a Negative Electrode Material for Potassium-Ion Batteries

Abstract: As one strategy for increasing energy density of K-ion batteries, electrochemical behavior of Sn oxides (SnO and SnO2) was studied as a negative electrode material. X-ray photoelectron spectroscopy and X-ray diffraction revealed followings: SnO underwent phase separation at the first charge (reduction) process to form metallic Sn and potassium oxide, and reversible alloying reactions between the resulting Sn and K proceeded up to a composition of KSn or more. In contrast, SnO2 showed little electrochemical rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 30 publications
1
28
0
2
Order By: Relevance
“…A few conversion materials were also reported as possible negative electrode for KIB such as Co 3 O 4 -Fe 2 O 3 , tin oxides or antimony and tin sulfides (Lakshmi et al, 2017;Sultana et al, 2017b;Shimizu et al, 2018). Shimizu et al reported the electrochemical activity of SnO, which is irreversibly converted into tin nanoparticles embedded in a stable matrix of K 2 O.…”
Section: Alloying and Conversion Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few conversion materials were also reported as possible negative electrode for KIB such as Co 3 O 4 -Fe 2 O 3 , tin oxides or antimony and tin sulfides (Lakshmi et al, 2017;Sultana et al, 2017b;Shimizu et al, 2018). Shimizu et al reported the electrochemical activity of SnO, which is irreversibly converted into tin nanoparticles embedded in a stable matrix of K 2 O.…”
Section: Alloying and Conversion Electrodesmentioning
confidence: 99%
“…Shimizu et al reported the electrochemical activity of SnO, which is irreversibly converted into tin nanoparticles embedded in a stable matrix of K 2 O. This matrix hinders the aggregation of the tin nanoparticles, which then undergo alloying reaction with K (Shimizu et al, 2018). Interestingly, SnO exhibits a discharge capacity around 200 mAh/g during 30 cycles, whereas SnO 2 appears to be inactive.…”
Section: Alloying and Conversion Electrodesmentioning
confidence: 99%
“…Besides the carbonaceous anodes (graphite, soft carbon, hard carbon, etc.) which are being explored vigorously but yield a relatively low specific capacity, metal oxides, such as iron oxides, molybdenum oxides, niobium pentoxides, tin oxides, and titanium oxides, are interesting anode candidates considering their high gravimetric and volumetric specific capacity, which are able to provide high performance anodes for KIBs . For example, antimony oxide (Sb 2 O 3 ) possesses a theoretical capacity as high as 1103 mAh g −1 for KIBs through both conversion reactions and alloy reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Because of the natural abundance of potassium, a similar redox potential of potassium to lithium, and the low cost, potassiumion batteries (KIBs) serve as a promising substitution to LIBs, [6][7][8][9][10][11] especially attractive in the largescale energy storage systems which strive intensively to lower the price to be competitive with other energy storage techniques. which are being explored vigorously but yield a relatively low specific capacity, [17][18][19][20][21][22][23][24][25][26][27] metal oxides, such as iron oxides, [28] molybdenum oxides, [29,30] niobium pentoxides, [31] tin oxides, [32] and titanium oxides, [33] are interesting anode candidates considering their high gravimetric and volumetric specific capacity, which are able to provide high performance anodes for KIBs. [12][13][14][15][16] Therefore, searching for the high performance KIBs anode (a critical component of KIBs) to alleviate the dramatic volume change is highly demanded to build high performance KIBs.…”
mentioning
confidence: 99%
See 1 more Smart Citation